Trajectories of Autism Severity in Early Childhood. - Venker, Courtney; Ray-Subramanian, Corey; Bolt, Daniel; Weismer, Susan (Journal of Autism & Developmental Disorders, 2014)
Relatively little is known about trajectories of autism severity using calibrated severity scores (CSS) from the Autism Diagnostic Observation Schedule, but characterizing these trajectories has important theoretical and clinical implications. This study examined CSS trajectories during early childhood. Participants were 129 children with autism spectrum disorder evaluated annually from ages 2½ to 5½. The four severity trajectory classes that emerged-Persistent High ( n = 47), Persistent Moderate ( n = 54), Worsening ( n = 10), and Improving ( n = 18)-were strikingly similar to those identified by Gotham et al. (Pediatrics 130(5):e1278-e1284, ). Children in the Persistent High trajectory class had the most severe functional skill deficits in baseline nonverbal cognition and daily living skills and in receptive and expressive language growth.